Making Simple Repairs: Repairing Screens - Mary N. Harrison (EDIS, 2019)
Holes in your screens allow insects, including flies, mosquitoes, and cockroaches to enter your home. This problem is easy to fix. This document is FCS5234-09, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.